Influence of various schemes of pathogenetic treatment on the state of prooxidant-antioxidant homeostasis on patients with acute hepatitis B and concomitant use of alcohol in hepatotoxic doses - Rуabokon, O. V.; Furyk, O. O.; Ushenina, N. S.; Рябоконь, Олена Вячеславівна; Фурик, Олена Олександрівна; Ушеніна, Ніна Степанівна; Рябоконь, Е. В.; Фурик, Е. А.; Ушенина, Н. С. (My University, 2014)
The study involved 133 patients with acute hepatitis B aged from 18 to 60 years. The article shows that in patients with acute hepatitis B and concomitant chronic consumption of alcohol in hepatotoxic doses consumption, the height of disease is characterized by larger disturbances in prooxidant-antioxidant regulation due to the higher level of aldehyde phenylhydrazone of spontaneous oxidative modification of blood proteins and nitrites, which is combined with the low L-arginine content in blood serum. The period of convalescence in these patients is characterized by a higher level of aldehyde phenylhydrazones and ketone phenylhydrazones of spontaneous oxidative modification of blood proteins, a higher content of nitrites in combination with low L-arginine content in the blood serum, as compared with patients without concomitant liver disease. The use of L-arginine hydrochloride (Tivortin) and thiotriazoline in the treatment of patients with acute hepatitis B with chronic consumption of alcohol in hepatotoxic doses improves antioxidant-prooxidant processes by reducing the content of nitrites and ketone phenylhydrazones of spontaneous oxidative modification of blood proteins, increased content of L-arginine and catalase activity in blood serum, contributes to the normalization of alanine aminotransferase activity, and increased frequency of HBeAg — anti-HBe seroconversion compared with patients who are treated using only basic agents. Обстежені 133 хворі на гострий гепатит В віком від 18 до 60 років. У роботі показано, що у хворих на гострий гепатит В із супутнім хронічним вживанням алкоголю в гепатотоксичних дозах розпал захворювання характеризується більшими порушеннями прооксидантно-антиоксидантної регуляції за рахунок вищого рівня альдегідфенілгідразонів спонтанної окисної модифікації білків крові та нітритів, що поєднується з низьким умістом L-аргініну в сироватці крові. Період реконва лесценції в цих хворих характеризується вищим рівнем альдегідфенілгідразонів й кетонфенілгідразонів спонтанної окисної модифікації білків крові, вищим умістом нітритів у поєднанні з низьким умістом L-аргініну в сироватці крові порівняно з хворими без супутнього ураження печінки. Залучення L-аргініну гідрохлориду (Тівортін) та тіотриазоліну до лікування хворих на гострий гепатит В із хронічним вживанням алкоголю в гепатотоксичних дозах сприяє поліпшенню прооксидантно-антиоксидантних процесів за рахунок зниження вмісту нітритів і кетонфенілгідразонів спонтанної окисної модифікації білків крові, підвищення вмісту L-аргініну й активності каталази в сироватці крові, сприяє нормалізації активності аланінаміно-трансферази та збільшенню частоти сероконверсії HBeAg — anti-HBе порівняно з хворими, у лікуванні яких використовували лише базисні засоби. Обследованы 133 больных острым гепатитом В в возрасте от 18 до 60 лет. В работе показано, что у больных острым гепатитом В с сопутствующим хроническим употреблением алкоголя в гепатотоксических дозах разгар заболевания характеризуется большими нарушениями прооксидантно-антиоксидантной регуляции за счет высокого уровня альдегидфенилгидразонов спонтанной окислительной модификации белков крови и нитритов, что сочетается с низким содержанием L-аргинина в сыворотке крови. Период реконвалесценции у этих больных характеризуется высоким уровнем альдегидфенилгидразонов и кетонфенилгидразонов спонтанной окислительной модификации белков крови, высоким содержанием нитритов в сочетании с низким содержанием L-аргинина в сыворотке крови по сравнению с больными без сопутствующего поражения печени. Добавление L-аргинина гидрохлорида (Тивортин) и тиотриазолина к лечению больных острым гепатитом В с хроническим употреблением алкоголя в гепатотоксических дозах способствует улучшению прооксидантно-антиоксидантных процессов за счет снижения содержания нитритов и кетонфенилгидразонов спонтанной окислительной модификации белков крови, повышению содержания L-аргинина и активности каталазы в сыворотке крови, способствует нормализации активности аланинаминотрансферазы и увеличению частоты сероконверсии HBeAg — anti-HBe по сравнению с больными, в лечении которых использовали только базисные средства.
Вплив різних схем патогенетичного лікування на стан прооксидантно-антиоксидантного гомеостазу у хворих на гострий гепатит В із супутнім хронічним вживанням алкоголю в гепатотоксичних дозах
Влияние различных схем патогенетического лечения на состояние прооксидантно-антиоксидантного гомеостаза у больных острым гепатитом B с сопутствующим хроническим употреблением алкоголя в гепатотоксических дозах
Keywords: acute hepatitis B; prooxidant-antioxidant homeostasis; alcohol; L-arginine hydrochloride; thiotriazolin; гострий гепатит В; прооксидантно-антиоксидантний гомеостаз; алкоголь; L-аргініну гідрохлорид; тіотриазолін; острый гепатит В; прооксидантно-антиоксидантный гомеостаз; алкоголь; L-аргинина гидрохлорид; тиотриазолин